Supplementation with a Novel Combination of Fruits and Vegetables Prevented High Fat Diet-Induced Cognitive Impairment in Mice. (29th May 2020) - Guo, Weimin; Shukitt-Hale, Barbara; Wu, Dayong; Li, Lijun; Ortega, Edwin; Liu, Yankun; Thomas, Michael; Nikolova-Karakashian, Mariana; Meydani, Mohsen; Meydani, Simin
Abstract: Objectives: Dementia and cognitive decline are typical age-related neurological disorders. However, obesity has been linked to premature senescence manifestations in various systems including the central nervous system. Nutritional interventions play a role in curbing obesity-associated disorders. Epidemiological studies suggest that increased consumption of fruits and vegetables (F&V) is associated with a reduced risk of cognitive impairment and dementia. The objective of this study was to investigate the causal role of F&V consumption in prevention of high fat diet-induced cognitive impairment in mice. Methods: Freeze-dried powder of a mixture of 24 F&V was added into the animal diets. Male C57BL/6 J mice (6 wk) were randomly assigned to one of the three diet groups (12/group): low fat (LF, 10% kcal fat), high fat (HF, 45% kcal fat), and HF plus 15% F&V (HF + F&V). The novel object recognition test was used to evaluate cognitive function at 17 weeks. After 20 weeks, mice were euthanized. Blood and liver were collected and biochemical variables and gene expression levels were determined. Fecal microbiota was characterized by 16S rRNA sequencing. Results: Compared to the LF group, mice fed the HF diet for 17 weeks had significant cognitive impairment. F&V supplementation significantly reduced the HF diet-induced cognitive impairment. Further, compared to mice fed the LF diet, those fed the HF diet had significantly higher levels of liver lipid peroxides (measured as MDA), and circulating pro-inflammatory cytokines and sphingolipid ceramides, all of which are known to contribute to neuroinflammation and cognitive deficits. These HF diet-induced adverse effects were significantly reduced in mice fed the HF + F&V diet. In addition, F&V supplementation alleviated HF diet-induced gut dysbiosis and greatly reduced abundance of some of the bacteria associated with inflammation. Conclusions: This study provides evidence for the causal role of F&V intake in preventing high fat diet-induced cognition impairment in mice. The beneficial effects of F&V supplementation in improving cognitive function might be due to F&V-induced changes in gut dysbiosis, inflammatory cytokines, and ceramides. Funding Sources: This material is based upon work supported by the U.S. Department of Agriculture — Agricultural Research Service (ARS), under Agreement No. 58-1950-4-003.